Endoscopic electrocauterization for management of chronic perineal sinus following abdominoperineal resection. Issue 5 (17th May 2022) - Larson, Brandon; Azizi, Shayan; Ma, Truong
Abstract: We present a case of a chronic perineal sinus following abdominoperineal resection with management via endoscopic electrocauterization. This patient presented with 1 year of bloody, mucus drainage from a perineal wound following abdominoperineal resection for anastomotic leak and stricture from a remote low anterior resection for T2N1 rectal cancer. We describe a novel use of endoscopic electrocautery to debride, de-epithelialize and ultimately eliminate the sinus cavity. The patient's postoperative course was uncomplicated and reported decreased drainage at 2- and 4-week postoperative follow-up. Long-term plans include sequential drain downsizing to facilitate cavity closure. Our findings suggest that endoscopic electrocauterization can safely and effectively reduce chronic perineal sinus drainage to facilitate cavity elimination, while avoiding morbidity associated with more invasive operative interventions.